A Study on Impact of GST: Business Review - et al., Kiran Ajeev (International Journal of Control and Automation, 2019)
The introduction of GST had lead to cost reduction throughout the business cycle from manufacturer to retailer and to the final consumer. The implementation of GST will lead to the reduction in the product prices throughout the business cycle. However, there is a substation in the product cost. The majority of products are still categorised in the high market.  Companies are facing many issues in common portal. The effectiveness of GST Sava Kendra set up by government in order to facilitate business is still questionable. Also, government is better to address many of the concerns in tax filling, input tax credit, refund mechanism, export & imports.